Dielectric and Design and Experimental Study of GIS Gas Chamber HF and Micro Water Dual Fiber Laser Detection System. Issue 1 (June 2021) - Shiling, Zhang; Xiaozhe, Zeng
Abstract: HF gas and trace moisture content, as the primary characteristic by-products of SF6 gas decomposition reaction, are of great significance to the fault diagnosis of high voltage SF6 gas insulated high voltage power equipment. In this paper, the typical discharge fault types in GIS are analyzed, and the decomposition products corresponding to different discharge types are summarized. The physical and chemical mechanism of HF generation in the early dissociation process of SF6 and under certain micro water and micro oxygen conditions is explained, and the experimental platform is built to carry out the simulation generation experiment of HF gas and micro water. The results show that choosing the best target absorption line suitable for sensitive and selective gas sensing can eliminate interference, simplify the system and reduce the cost. Furthermore, under the experimental conditions, the self-developed TDLAS online detection technology is used to realize the effective detection of HF gas and trace water in GIS discharge room. The 1278nm and 1392nm laser sources are selected respectively, and the TDLAS technology based on dual fiber time-sharing multiplexing is feasible for HF and trace water measurement. The stability and reliability of the technology are verified, which can provide effective technical support for on-line detection of HF gas in GIS, and has good engineering application value.